Corporate Social Responsibility on Innovation and Creativity in the Workplace - Ejoh, Ejiro; A. Omoile, Patrick (Malikussaleh Social and Political Reviews, 2023)
Corporate Social Responsibility (CSR) has transformed from a philanthropic gesture to a fundamental component of company strategy in the modern economic environment. This paper seeks to explain how corporate social responsibility (CSR) practices influence employee motivation, engagement and overall organizational performance. Data used for the study were obtained through secondary sources, which included descriptive examinations of documents that contain crucial information about the topic under discourse. Through examination of various theoretical frameworks and empirical studies, the study discovered that CSR has positively influenced employee motivation and engagement, which has led to increased innovative behaviour. On the strength of the findings, the study recommends that organizations prioritise CSR practices to drive innovation and creativity.